The manifestation of praise for the Prophet in the scientific systems of Al-Nudhi (the system of the work of formulation as a model) - Radwan, Hadi (Sulaimani Journal for Humanities, 2024)
Sheikh Ma'ruf al-Nawdahi al-Barzanji was one of the prominent scholars and distinguished writers of the twelfth and thirteenth centuries AH. He dedicated eighty years of his life to teaching and writing, and was renowned for his beneficial scientific treatises on various sciences and arts. It is worth noting that he stated in some of his poems that his approach was to systematize the sciences. He was also famous for his magnificent literary quintets, most of which were in praise of the Prophet Muhammad. Some researchers say that his quintets were stronger than his poetry, as he was a master of the former and possessed a vast imagination, while in the latter he was more imitative and a follower. In any case, it was no exaggeration to call al-Nawdahi the "Busiri of the Kurds." It is noteworthy that al-Nawdhi did not neglect praise of the Prophet in his scientific poems. Many of the examples within them are themselves praise of the Prophet, and the introductions to these poems also contain sublime verses in praise of the Prophet. Thus, al-Nawdhi's poetic talent extended even to his scientific writings, which are usually expected to be devoid of imagination, emotion, and refined sentiment. Among these poems is "The Art of Rhetoric," in which al-Nawdhi versified the book "The Liberation of Rhetoric" by the scholar Muhammad ibn Adam al-Balaki. Many examples in this poem are praise of the Prophet, demonstrating the sincerity of al-Nawdhi's emotion, the purity of his intellect, and the strength of his mastery in this art. This article explores the themes related to and belonging to the Prophetic praise in the system of formulating work. Many examples of this system are from the ideas of Al-Nodhi, and this work reminds us of what the scholar Al-Bitoshi did in the system of “Kifayat Al-Ma’ani”. No wonder, for Al-Nodhi drew from his literary source and benefited from his style of composition and writing.
Keywords: Didactic poetry; praise of the Prophet; the Nawdhi; the system of composition